The new IEEE standard dictionary of electrical and electronics terms - Booth, Christopher J. (IEEE New YorkUS, 1993)
Includes all terms and definitions that have been standardized previously by IEEE as well as many from American National Standards and the International Electrochemical Vocabulary. This edition adds definitions from IEEE standards published since the 1988 edition up to those approved in December of 1991.